2003
DOI: 10.1238/physica.regular.067a00453
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Excitation of ULF Atmosphere–Ionosphere Waves and Magnetic Perturbations Caused by ELF Seismic Acoustic Bursts

Abstract: Nonlinear excitation of ultra-low frequency (ULF) atmosphere-ionosphere waves by extremely low frequency (ELF) seismic acoustic bursts is discussed. An analysis of the nonlinear transformation of ELF acoustic waves (f ~ 100 Hz) into ULF (f ≤ 1Hz) waves is presented. The ELF wave is excited as the burst-like envelope of a finite transverse scale by the seismic motion of the Earth’s surface. Then, it propagates upwards and is subject to both nonlinearity and dissipation. Nonlinearity leads to the generation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In the present paper, we continue the experimental and theoretical works (Parrot et al, 2007;Koshovyy, 1999;Kotsarenko et al, 1999;Koshevaya et al, 2005;Grimalsky et al, 2003) on the penetration of SWs excited by the PSG into the atmosphere and ionosphere. We formulate and solve the new problems not considered in previous papers (Koshevaya et al, 2005;Krasnov and Kuleshov, 2014;Rapoport, et al, 2004).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…In the present paper, we continue the experimental and theoretical works (Parrot et al, 2007;Koshovyy, 1999;Kotsarenko et al, 1999;Koshevaya et al, 2005;Grimalsky et al, 2003) on the penetration of SWs excited by the PSG into the atmosphere and ionosphere. We formulate and solve the new problems not considered in previous papers (Koshevaya et al, 2005;Krasnov and Kuleshov, 2014;Rapoport, et al, 2004).…”
supporting
confidence: 58%
“…Moreover, in order to search the seismogenic effects in the ionosphere, it is necessary to unify the well-developed model of the electromagnetic channel to seismo-ionospheric coupling (Molchanov et al, 1995;Rapoport et al, 2004b;Grimalsky et al, 1999;Pulinets and Boyarchuk, 2004;Sorokin and Hayakawa, 2013) with the model of the acoustic channel (Gokhberg and Shalimov, 2000;Rapoport et al, 2004aRapoport et al, , 2009Koshevaya et al, 2002;Grimalsky et al, 2003;Zettergren and Snively, 2015;Iyemori et al, 2015). Traditionally, AGWs and electromagnetic waves have been considered as the basis of two main competitive mechanisms of seismo-ionospheric coupling (Sorokin and Hayakawa, 2013;Klimenko et al, 2011;Pulinets and Boyarchuk, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the signals are originating from subsurface near a hypocenter, then the idea of evanescent propagation like in Grimalsky et al (2003), or an analog to the seismic "head wave" discussed in Stein and Wysession (2003) that occurs at interfaces between layers of differing indices of refraction, might be a useful framework for discussing them.…”
Section: Discussionmentioning
confidence: 99%
“…When the transverse scale ρ 0 ∼1-10 km, the diffraction is not essential for the ELF wave but it can decrease the peak amplitudes of the ULF part. The results of the numerical simulations are analogous to the nonlinear propagation of acoustic waves in the lithosphere, but the frequency range is lower and the vertical scales are greater (see Grimalsky et al, 2003). The simulations have shown that there is an effective nonlinear interaction of the ELF and ULF atmospheric acoustic waves and a nonlinear excitation of the ULF atmosphereionosphere waves caused by the ELF seismic acoustic bursts on the surface of the Earth.…”
Section: Nonlinear Passage Through the Lithospherementioning
confidence: 71%